A Foliar application silicon enchances drought tolerance in Fennel - M. R. Asgharipour; Hasan Mosapour (Journal of Animal and Plant Sciences, 2016)
The objectives of this study were to evaluate improving the drought toleration by the function of Silicon (Si) in fennel. The experimental design was a split-plot with three irrigation treatments: irrigation at 90, 75 and 60% of FC as main treatments, and five levels of Si foliar sprays (0, 2.5, 5, 7.5 and 10 mM) comprising the sub-treatments that were exerted with three replicates. The experiment was carried out during 2014 at the Zabol University Research Farm, Zabol, Iran. Water stress significantly decreased LAI, plant height, one-thousand seed weight, seed yield, concentrations of calcium and potassium in seed, while stimulated concentration of proline, soluble sugars and sodium in seed, as well as concentration of Si in leaf. Si application increased concentration of proline and soluble sugars in seed, LAI, seed yield, essentialoil percentage, concentration of sodium andpotassium in seed by 24, 13, 20, 17, 31, 41, 24 and 9%, respectively, over those of the control. The greatest essential oil percentage (2.17%) was achieved in plant sprayed with 7.5 mM of Si under mild water stress. These results suggested that Si spraying improved growth and physiological indices hence could increase the ability of plants to resistance water stress.
Keywords: Essential oil; Proline; Potassium; Yield and yield attributes